Adult Basic Education and the Preparation of South African Youth: Towards an Agenda for the Future. (1st March 2016) - Oduaran, Akpovire
Abstract: This descriptive paper proceeds with the assumption that the expectations, aspirations and challenges of the South African youth of the future could be so intricate that no single system of education can adequately satisfy their demands for learning within one segment of the entire lifespan. This is one major reason why adult basic education could become so critical and worthy of an academic discourse of this nature even as South Africa grapples with a myriad of strategies for meeting the needs of its youth. Adult basic education should be one of the critical human resource development strategies South Africa needs because it continues to harbor a large number of adult illiterates many of whom are youth and 55 percent of them female. The Kha ri Gude Mass Literacy Campaign launched in February, 2008 has been planned to ensure that between 14 th April, 2008 and the end of 2015, South Africa should be totally rid of its burden of illiteracy. But the challenges the South African youth of the future must contend with go beyond illiteracy. This discourse therefore makes some major propositions for consideration and immediate action in anticipation of the coming of a growing and restive population that could be stirred up by social and economic winds in an increasingly connected wider world